Shelf life study of sweet potato cookies (Ipomoea batatas L.) with the incorporation of yellow pumpkin (Cucurbita moschata Durch) - Fishi, Ana Nadiya Afinatul; Firdaus, Maisa Amatillah; Amelianawati, Mae; Khairiah, Khairiah (Advances in Food Science, Sustainable Agriculture and Agroindustrial Engineering (AFSSAAE), 2025)
The shelf life of yellow sweet potato cookies was determined based on the desirable quality, primarily characterized by acceptable crunchiness to consumers. This study employed the Accelerated Shelf Life Testing (ASLT) model using a critical moisture content approach. Estimating shelf life begins with an initial moisture content test (Mi) and then continues with determining the necessary moisture content (Mc) through a hedonic test on cookies stored without packaging at a room temperature of 30℃ and 75% relative humidity (RH) over a period of 0-7 hours. Determination of equilibrium moisture content (Me) was carried out by measuring the moisture content of cookies at RH 30-83% which was conditioned using a saturated salt solution of MgCl2, NaNO2, NaCl, and KCI. The relationship between water activity (aw) and equilibrium moisture content was described in the Guggenheim-Anderson-de Boer (GAB), Brunauer-Emmett-Teller (BET), and Henderson isotherm sorption curve models. These models were tested for accuracy using the Mean Relative Determination (MRD) formula. The Mean Relative Determination (MRD) formula, with models having an MRD value of less than 5% being considered suitable for shelf life determination. The research results showed the findings revealed that the GAB model, with a type II sigmoid isothermic curve and an MRD value of 4.95%, was the most appropriate for predicting the shelf life of yellow sweet potato cookies. The best estimation of shelf life of yellow sweet potato cookies was at a temperature of 30℃ and 63-65 % RH using metalized plastic packaging with a shelf life of 10.6 months.